PENGARUH PENGGANTIAN ABU BATU MENGGUNAKAN ABU CANGKANG PENSI PADA CAMPURAN ASPAL ( AC-WC ) DENGAN PENGUJIAN MARSHALL - Misbah Misbah; Usratul Hidayat (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Good road construction is needed to improve the welfare of society in general and the economy of the population in particular. The current high cost of road construction and maintenance, it would be better for road construction to be focused on improving road quality, both in terms of financing, implementation methods and in terms of road maintenance so that maximum results are obtained and roads can last according to the planned age. Road pavement construction often experiences damage before the design life is reached. Causes of road damage include: excessive vehicle loads, influence of asphalt factors, sub-optimal road maintenance and execution of works that do not meet the specifications of the Ministry of Public Works.To improve the quality of road pavement construction, it is necessary to conduct research on mixed innovations used or adding other additives to the pavement construction mixture, so that better mixed quality is obtained. One of the types of research that can be done is to use the experimental method by conducting experiments in the laboratory by analyzing the effect of replacing rock ash using pensi shell ash on asphalt mixture (AC-WC) with the Marshall test.From the results of the research with the Marshall test that has been carried out, there are 4 property values that do not meet the requirements, namely: VIM, VFA, Flow and Marshall Quotient (MQ). Thus, it can be concluded that replacing rock ash with pensi shell ash in the AC-WC mixture cannot be used for the AC-WC mixture. Keywords: Pensi Shell Ash, Marshall Characteristics